PROSPECTIVE TEACHER STUDENTS' ABILITY IN WRITING SPSS POCKET BOOKS - Nailul Authary; Cut Indah Lestari; Rathma Nur Masyitah; Fitriyasni Fitriyasni (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
The lecture process that students undergo for one semester is to fulfill the demands of the independent curriculum. During lectures, students are asked to provide output from projects carried out to strengthen the profile of Pancasila students. The aim of this research is to examine the effectiveness of the SPSS pocket book. This research is a type of research and development or RD. This research was carried out at the Tadris Mathematics Study Program, Faculty of Islamic Religion, Muhammadiyah University of Aceh. The subjects in this study were 2 people. The results of this research are very suitable for use in the classroom. This is proven by the validation results, namely the percentage value from media experts of 90.5% and material experts of 96%